EFEKTIFITAS INDONESIA UNTUK MENJAGA KEANEKARAGAMAN HAYATI LAUT DALAM CORAL TRIANGLE INIATIATIVE ON CORAL REEFS, FISHERIES AND FOOD SECURITY (CTI-CFF) - Ridona "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The Asia-Pacific's Coral Triangle is defined by its extremely high marine biodiversity. Over one hundred million people living in its coastal zones use this biodiversity to support their livelihoods. Hundreds of millions more derive nutritious food directly from the region′s marine resources and through local, regional and global trade. Biodiversity and its values to society are threatened by demographic and habitat change, rising demand, intensive harvesting and climate change. In partnership with international conservation organizations and development funders, the governments of the region′s six countries have come together to develop the Coral Triangle Initiative (CTI) on Coral Reefs, Fisheries and Food Security. The focus of this research is Efektifity Indonesia for ecosystem in the CTI-CFF. This study uses the theory of International Organization and the use of perspective Neo Liberalism. The data is taken from books, journals and websites.